Academic doctors' views of complementary and alternative medicine (CAM) and its role within the NHS: an exploratory qualitative study - Shaw Alison; Maha Nita (BMC, 2007)
Abstract Background There has been a marked increase in the use of complementary and alternative medicine (CAM) in the UK population in recent years. Surveys of doctors' perspectives on CAM have identified a variety of views and potential information needs. While these are useful for describing the proportions of doctors who hold particular attitudes towards CAM, they are less helpful for understanding why. In addition, while the views of non-academic doctors have begun to be studied, the perspective and rationales of academic doctors remains under-researched. It seems important to investigate the views of those with a research-orientation, given the emphasis on the need for more scientific evidence in recent debates on CAM. Methods This exploratory study used qualitative methods to explore academic doctors' views of CAM and the rationales they provided for their views. A purposeful sampling strategy was used to identify doctors with a dual clinical and academic role in the Bristol area, with an anticipated variety of views on CAM. Semi-structured interviews were conducted with nine doctors. The data were analysed thematically, drawing on the Framework Approach. Results The doctors expressed a spectrum of views on CAM, falling into three broad groups: the 'enthusiasts', the 'sceptics' and the 'undecided'. Scepticism or uncertainty about the value of CAM was prominent, except among those practising a form of CAM. A variety of rationales underpinned their perspectives on CAM, a key recurring rationale being their perspective on the scientific evidence base. The main themes arising included: the role of doctors' professional experiences of conventional medicine and CAM in shaping their attitudes towards CAM, doctor-patient communication about CAM and patient disclosure, whether there is a need for training and education in CAM for doctors, a hierarchy of acceptability of CAM and the nature of evidence; and the role of CAM within the NHS. Conclusion Despite the caution or scepticism towards CAM expressed by doctors in this study, more open doctor-patient communication about CAM may enable doctors' potential concerns about CAM to be addressed, or at least enhance their knowledge of what treatments or therapies their patients are using. Offering CAM to patients may serve to enhance patients' treatment choices and even increase doctors' fulfilment in their practice. However, given the recurring concerns about lack of scientific evidence expressed by the doctors in this study, perceptions of the evidence base may remain a significant barrier to greater integration of CAM within the NHS.